Pengembangan UI/UX Sistem Pengelolaan Inventori Menggunakan Metode Design Thinking - Widjaja, Stephanus; Wicaksono, Adityo Putro; Widayati, Yohana Tri; Nugroho, Mohamad Fajarianditya; Sandeas, Dhegih (JOINS (Journal of Information System), 2024)
System development requires an interface design that suits the user, this is so that the system can be used fully without reducing or ignoring its main functions. Dwi Jaya Store which operates in the wholesale and retail product sales sector faces challenges such as managing suppliers which may be more than one supplier, managing product orders to suppliers based on inventory levels, managing product returns to suppliers if there are defects or damage, managing the traffic of goods from main warehouse to shops and report management. Dwi Jaya Store requires an inventory system that is easy to use but does not reduce the performance and function of the system. This research aims to produce a prototype inventory system that users use easily. This research uses the design thinking method, usability testing method, and Figma as a design tool. This research produced a prototype with a usability testing value of 78.4% which was included in the Good Application category.